Architecture and Pedagogy in France: 1970, an aborted revolution - Chatelet, Anne-Marie (Historia y Memoria de la Educación, 2020)
According to historian Antoine Prost, education in France is marked by two periods of profound reform. The first (1880-1902) occurred during the Third Republic and the second (1960-1985) was set in motion under de Gaulle. From an architectural point of view, the former gave rise to the Jules Ferry school, while the latter sought to introduce the English open-space school model into France. Taking the example of the École Saint-Merri, built in Paris between 1971 and 1973, this article examines the impact of this second reform from an architectural point of view.